Loyalitas Pelanggan Pada Business-To-Business: Pengaruh Kualitas Pelayanan - Lulu Marjani; Mamun Sutisna (Jurnal Riset Bisnis dan Investasi, 2019)
Customer loyalty is the key to the success of every company, especially in business to business (B2B) markets where the company has a long-term orientation business. Due to the importance of maintaining the quality of service to create customer loyalty, this research was conducted to determine the effect of service quality on customer loyalty on business to business. This research uses 117 business to business customers as respondents. The results of this study illustrate that service quality has an effect of 54,6% on customer loyalty.